The Role of International Commercial Arbitration in Resolving Disputes Arising from the DBOT Contract - Muhammad, Asmaa Abd; Ameen, Khalis Nafi (Journal of Ecohumanism, 2024)
The International Federation of Consulting Engineers (FIDIC) is a prominent contributor to activating the role of arbitration in resolving disputes as one of the means resorted to instead of the judiciary and what arbitration is characterized by characteristics that facilitate the parties to resolve the dispute presented to them after exhausting all friendly means from the Dispute Resolution Council and other friendly means, which made resorting to inevitable arbitration in investment contracts and the DBOT contract represents one of the contractual models issued by (FIDIC) and the most appropriate for investment contracts, especially if the investor is foreign in his contract with the state or one of its public institutions, as the investor seeks to Preserving his rights by stipulating certain conditions that protect him from being subject to the law or national judiciary of the state party to the contract. Perhaps the FIDIC model (DBOT) has taken this issue into account by including a condition requiring the parties to resort to arbitration to settle disputes between them if other amicable methods fail to resolve the dispute, which requires research into the subject to clarify the definition of Arbitration, its types, and the procedures included in the Golden Contract Model (DBO) in considering the dispute until the issuance of the arbitration decision, compared to what is included in the standard documents issued by the Iraqi Ministry of Planning based on Circular No (4/7/4185) dated (24/2/2016) and other legislation related to the research topic.